Characterization of LysB4, an endolysin from the Bacillus cereus-infecting bacteriophage B4 - Son, Bokyung (BioMed Central, 2012)
BACKGROUND: Bacillus cereus is a foodborne pathogen that causes emetic or diarrheal types of food poisoning. The incidence of B. cereus food poisoning has been gradually increasing over the past few years, therefore, biocontrol agents effective against B. cereus need to be developed. Endolysins are phage-encoded bacterial peptidoglycan hydrolases and have received considerable attention as promising antibacterial agents. RESULTS: The endolysin from B. cereus phage B4, designated LysB4, was identified and characterized. In silico analysis revealed that this endolysin had the VanY domain at the N terminus as the catalytic domain, and the SH3_5 domain at the C terminus that appears to be the cell wall binding domain. Biochemical characterization of LysB4 enzymatic activity showed that it had optimal peptidoglycan hydrolase activity at pH 8.0-10.0 and 50°C. The lytic activity was dependent on divalent metal ions, especially Zn(2+). The antimicrobial spectrum was relatively broad because LysB4 lysed Gram-positive bacteria such as B. cereus, Bacillus subtilis and Listeria monocytogenes and some Gram-negative bacteria when treated with EDTA. LC-MS analysis of the cell wall cleavage products showed that LysB4 was an L-alanoyl-D-glutamate endopeptidase, making LysB4 the first characterized endopeptidase of this type to target B. cereus. CONCLUSIONS: LysB4 is believed to be the first reported L-alanoyl-D-glutamate endopeptidase from B. cereus-infecting bacteriophages. The properties of LysB4 showed that this endolysin has strong lytic activity against a broad range of pathogenic bacteria, which makes LysB4 a good candidate as a biocontrol agent against B. cereus and other pathogenic bacteria.